English Loanwords in Urdu Language: A Study of Borrowing - Ahmad, Zuhair; Khan, Ilyas (JL3T (Journal of Linguistics, Literature and Language Teaching), 2024)
When a new object or activity or idea enters in a culture, the word or words which express it may be borrowed. The most basic function of a loanword is communicating the new object or idea. A culture may elect to use its own resources (as ‘horsepower’ for a steam locomotive engine) for the new item Hoffer, (2002). The present research aims at examining the English borrowed words into Urdu language. It begins with Introduction to the borrowing in general and English with reference to Urdu in particular. It also discusses various forms of borrowing. English language has been in contact with Urdu during the British colonization in India. This has resulted into borrowing so many lexicons into Urdu which must be studied linguistically. It is argued that borrowing has enhanced the communicative range of Urdu lexicons. This is the qualitative study in its nature. Loanwords have been categorized in different domains. Then, the historical background of Urdu and English language interaction until now, and the processes, reasons that are involved in the borrowing of loanwords in Urdu from English language has been discussed.